Uji Aktivitas Antibakteri Campuran Ekstrak Biji Kelor (Moringa oleifera) dan Daun Kersen (Muntingia calabura) terhadap Pseudomonas aeruginosa dan Bacillus subtilis - Syuhuud Arumbinang Wajdi; Sri Kasmiyati; Susanti Puji Hastuti (Journal of Tropical Biodiversity and Biotechnology, 2017)
Moringa oleifera and Muntingia calabura leaves have been reported to have an antibacterial activity that could inhibit the growth of gram positive and negative bacteria. However, the antibacterial activity of mixed extracts of M. oleifera seeds and M. calabura leaves has not been widely reported. The purpose of this study was to test antibacterial activity of the mixed extract of M. oleifera seeds and M. calabura leaves on the growth of Pseudomonas aeruginosa and Bacillus subtilis. The experiment was conducted by agar disc diffusion method using three groups of extract treatments i.e. M.oleifera seeds extract, M.calabura leaves extract, and mixed extracts of M. oleifera seeds and M. calabura leaves with a ratio of 1: 1 (v / v). The extraction of M. oleifera seeds and M. calabura leaves was conducted by soxhlation method and using ethanol as solvent. The three groups of extract treatments with a concentration of 400 ppm, 800 ppm, 1200 ppm, and 1600 ppm were tested on P. aeruginosa. The antibacterial activity test of M. oleifera seed extract against B. subtilis carried out at the level of concentrations i.e. 150 ppm, 300 ppm, 450 ppm, 600 ppm, and 750 ppm, meanwhile,  M. calabura leaves extract was done at concentration 1500 ppm, 3000 ppm, 4500 ppm, 6000 ppm, and 7500 ppm. The result showed that the three groups of extract treatments possess antibacterial activity against P. aeruginosa. The mixed extracts of M. oleifera seeds and M. calabura leaves with a ratio of 1: 1 (v / v) at level concentration of 400 ppm and 800 ppm were tested against P. aeruginosa significantly increased, and at concentrations of 1200 ppm and 1600 ppm significantly decreased  the inhibition diameter of bacterial growth than the other extracts treatments. The antibacterial test results of M.oleifera seeds extract and M.calabura leaves extract against B. subtilis shows that increased concentrations of the extract significantly increase the inhibition diameter of bacterial growth especially at high concentrations ( 600 ppm and 750 ppm) on M. oleifera seeds extract, as well as 6000 ppm and 7500 ppm in M. calabura leaves extract.